Kalam Insha Talabi in Surah Yusuf - Sa'dina, Ahmad Midrar; Zaelani, Agung Ahmad (UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this research is to do a description-analysis of the elements of the word insha talabi in Surah Yusuf. This research uses qualitative methods through library research. This research was conducted by examining the distribution of selected verses in Surah Yusuf, which had not been studied before. In addition, it explores how the dynamics of interpretation in these selected verses and their relation to the content of the elements of the word insha talabi. The results and discussion of this study found that there are 28 verses about amr, 5 verses about nahi, 12 about istifham, 2 verses about tamanni, and 18 verses about nida. The study of these verses, among other things, is expected to reach the esoteric elements in each verse wisely and in accordance with objective scientific provisions so that the beauty of the style of Al-Qur'an as a whole in Surah Yusuf which is one of the best stories in the Al-Quran can be understood properly. Therefore, it is important to conduct this study and continue to explore its interpretation so that the compassion and wisdom of Yusuf's story can become a strong value in this life in various aspects.